Modern Views on the Neuropeptide Oxytocin. Part I. Oxytocin Structure, Synthesis, Excretion, Regulation, Inhibition and Metabolism. Oxytocin Receptors (Review) - Elena A. Leonova; Albina A. Bakhova; Irina L. Cherednik; Yulia V. Kashina; Aleksandr N. Ardelyan (Журнал медико-биологических исследований)
It is known that the behavioural reactions of animals and humans are controlled by a number of neuropeptides. This article examines the modern views of scientists on the physiological effects of oxytocin and its influence on the social behaviour, psychological state and somatoautonomic functions of humans and animals. In addition, the paper looks into studies on the correlation between insufficient oxytocin production and the pathogenesis of various mental diseases. Data on the structure, synthesis, metabolism and inactivation of oxytocin are presented. Information is provided on the regulation of oxytocin release under the influence of psychological factors and inhibition of oxytocin release into the central nervous system by a number of biologically active substances: glucocorticoids, testosterone, acetylcholine, nitric oxide and gamma-aminobutyric acid. Substances suppressing the physiological effect of oxytocin provoke hostility in animals and humans by reducing the effect of oxytocin on the amygdala, which is responsible for aggression. Further, the paper summarizes data on the synthesis of oxytocin on the periphery, in such organs as the corpus luteum, uterus, amnion, placenta, interstitial cells of the testes, adrenal glands, heart, dermis and thymus. Peripheral organs with the expression and binding of oxytocin receptors include macula densa cells, cardiomyocytes, nociceptive dorsal root ganglion neurons, retina, adipocytes and cells of the adrenal medulla. Oxytocin synthesis and oxytocin receptor expression have been detected in human skin fibroblasts and keratinocytes. These cells regulate processes involved in atopic dermatitis, such as proliferation, inflammation and reaction to oxidative stress in the skin. Questions about the location of oxytocin receptors, both in the central nervous system and beyond, have been discussed. The most studied brain regions expressing oxytocin receptors are the hypothalamus, prefrontal cortex, hippocampus and amygdala.